1967
DOI: 10.1007/bf00385291
|View full text |Cite
|
Sign up to set email alerts
|

�ber Zusammenh�nge zwischen dem CO2-Austausch und der Abgabe von Wasserdampf durch Bryophyllum daigremontianum Berg

Abstract: 1. The transpiration in leaves of Bryophyllum daigremontianum exactly follows the changes in consumption of atmospheric carbon dioxide (caused by the Crassulaceen acid metabolism) during the light and dark periods. After removal of the epidermis no distinct rhythm in the course of transpiration can be observed any more, whereas the characteristic CO2 exchange continues in an unchanged matter. For this reason we assume that the changing rate of CO2 uptake from the atmosphere determines the concentration of carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
1
1

Year Published

1972
1972
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(21 citation statements)
references
References 9 publications
1
18
1
1
Order By: Relevance
“…(14), while the results with Bryophyllum daigreinontianum demonstrate a continual reduction in nocturnal gas exchange once diurnal gas exchange is completely restricted (12). Recent seasonal results with Dudleya farinosa demonstrated a decrease in leaf conductivity to water vapor as drought-induced water stress increased (2).…”
Section: Methodsmentioning
confidence: 99%
“…(14), while the results with Bryophyllum daigreinontianum demonstrate a continual reduction in nocturnal gas exchange once diurnal gas exchange is completely restricted (12). Recent seasonal results with Dudleya farinosa demonstrated a decrease in leaf conductivity to water vapor as drought-induced water stress increased (2).…”
Section: Methodsmentioning
confidence: 99%
“…2) consists of a microcapillary (tip diameter: [3][4][5][6][7] ,um) filled with silicone oil and connected to a small pressure chamber containing a pressure transducer. When the microcapillary tip is introduced into a cell, the cell P pushes the oil back into '1 .…”
mentioning
confidence: 99%
“…These processes should follow diffusion kinetics, whereas the pressure-relaxation of individual cells measured by the probe is exponential and yields T,I2 (see Fig. 3 and equation 1 In fact, it can be calculated from gas-exchange curves in the literature (6,8,9) (23)(24)(25) and other plants (14) suggests even more that water relations are an important factor. However, Winter and Luttge (24) observed that, during the induction of CAM in M. crystallinum by high salinity (NaCl), the succulence of the leaves was reduced and the water content decreased.…”
mentioning
confidence: 99%
“…Under water stress conditions, salt-deprived plants using only the reductive pentose phosphate cycle pathway assimilated less carbon and were less efficient in their water use than salt-treated plants using predominately the CAM pathway. These results support the hypothesis that the ability to use the CAM pathway reduces the capacity for reductive pentose phosphate cycle fixation but permits higher productivity in water-limited environments.In plants exhibiting the CAM pathway of carbon fixation, the relative amounts of CAM and C33 used for external CO2 assimilation may vary with water availability (1,10,15,27), day-night temperature differentials (11, 26), or photoperiod (16). Generally, conditions which increase water stress favor CAM because the water use efficiency of CAM is greater than that of C3 (17).…”
mentioning
confidence: 99%
“…relative amounts of CAM and C33 used for external CO2 assimilation may vary with water availability (1,10,15,27), day-night temperature differentials (11,26), or photoperiod (16). Generally, conditions which increase water stress favor CAM because the water use efficiency of CAM is greater than that of C3 (17).…”
mentioning
confidence: 99%